Child trafficking: young people’s experiences of front-line services in England - Gearon, Alinka (The British journal of criminology, 2019)
This article reports findings from an innovative qualitative study with 20 young people who were trafficked into and within England and their experiences of front-line services. In practice, concepts of consent and coercion are problematized as inadequate determinants of child trafficking. Young people reported experiencing front-line practice as victim-blaming and punitive. The findings demonstrate that young people require a more welfare-orientated response, based upon being listened to, believed and with greater action taken to protect them from further harm. They extend policy debates by providing fresh insights into children’s experiences of trafficking and services, hitherto omitted. The findings support the depoliticizing of child trafficking policy, away from a criminal justice approach, and abandoning labelling children as ‘smuggled’ and ‘trafficked’.